2020
DOI: 10.1101/2020.06.22.165522
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Tissue-specific dynamic codon redefinition in Drosophila

Abstract: Stop codon readthrough during translation occurs in many eukaryotes, including Drosophila, yeast, and humans. Recoding of UGA, UAG or UAA to specify an amino acid allows the ribosome to synthesize C-terminally extended proteins. We previously found evidence for tissue-specific regulation of stop codon readthrough in decoding the Drosophila kelch gene, whose first open reading frame (ORF1) encodes a subunit of a Cullin3-RING ubiquitin ligase. Here, we show that the efficiency of kelch readthrough varies markedl… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 73 publications
(95 reference statements)
0
3
0
Order By: Relevance
“…Readthrough may occur when a near-cognate tRNA inserts an amino acid, and its efficiency varies across cell type and conditions. 42,43 We speculate that the conserved Ir56b PTC could provide a mechanism that allows the level of Ir56b to be modulated by environmental conditions such as salinity. Such a mechanism could have been lost in the cactophilic species that evolved in arid regions and that may have experienced a narrower range of salt concentrations or may have special needs to maintain salt balance.…”
Section: Ir56b Has a Conserved Functionmentioning
confidence: 97%
“…Readthrough may occur when a near-cognate tRNA inserts an amino acid, and its efficiency varies across cell type and conditions. 42,43 We speculate that the conserved Ir56b PTC could provide a mechanism that allows the level of Ir56b to be modulated by environmental conditions such as salinity. Such a mechanism could have been lost in the cactophilic species that evolved in arid regions and that may have experienced a narrower range of salt concentrations or may have special needs to maintain salt balance.…”
Section: Ir56b Has a Conserved Functionmentioning
confidence: 97%
“…Subsequently, ribosome profiling revealed differential ribosomal footprints in several other genes that show significant TR in samples derived from early embryos and S2 cells (Dunn et al, 2013). More recently, several studies in Drosophila have reported highest levels of TR in tissues of the CNS, mainly neurons (Chen et al, 2020; Hudson et al, 2020). These studies are concurrent with findings in mice, where the incidence of cell-type-specific TR was detected by analysis of TR in neurons and astrocytes in the CNS as well as peripheral tissues (Palazzo et al, 2020; Sapkota et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In the yeast Saccharomyces cerevisiae, the [PSI+] strain forms prion-like polymers of the abnormal eukaryotic release factor 3 (eRF3), which is implicated in translation termination and peptide release, resulting in a high level of readthrough across many genes 20 , including Phosphodiesterase 2 (PDE2), Interacting with mpp10p 3 (IMP3), and Bypass of stop codon 4 (BSC4) 10,21,22 . In Drosophila melanogaster, readthrough is estimated to affect over 300 genes 23,24 , such as kelch (kel) 12,25 , Synapsin (Syn) 26 , headcase (hdc) 27 , and traffic jam (tj) 13 . In (which was not certified by peer review) is the author/funder.…”
Section: Introductionmentioning
confidence: 99%